2020
DOI: 10.1111/raq.12522
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory quotient and the stoichiometric approach to investigating metabolic energy substrate use in aquatic ectotherms

Abstract: The respiratory quotient (RQ) has been used extensively as an index to evaluate metabolic energy expenditure in terrestrial animals including humans. In contrast, RQ use in understanding physiology and nutrition of aquatic ectotherms has been restricted due to technical challenges in measuring total CO 2 in water. With technical advances in measuring total CO 2 in water, RQ in aquatic ectotherms can be accurately determined and is potentially available as a valuable method. Here, we provide a comprehensive rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 222 publications
(704 reference statements)
0
7
0
Order By: Relevance
“…Interestingly, an even lower resting AQ (0.043) can be calculated from Ṁ Amm and ṀO 2 data reported by Simonik and Henry (2014) for 2‐day fasted C. maenas at similar temperature, even though both absolute rates were much higher in that study. Theoretically, if all aerobic metabolism were fueled by protein (amino acid) oxidation, the AQ would be 0.27 (Lauff & Wood, 1996; Wang et al, 2021a), so these AQ values would suggest that only 33% (present study) or 16% (Simonik & Henry, 2014) of resting metabolism is based on protein oxidation in the green crab. These values seem low relative to the few other measurements on moderately fasted carnivorous decapods, where AQs >0.135 indicated that protein was the major metabolic fuel (reviewed by Wang et al, 2021a, 2021b).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Interestingly, an even lower resting AQ (0.043) can be calculated from Ṁ Amm and ṀO 2 data reported by Simonik and Henry (2014) for 2‐day fasted C. maenas at similar temperature, even though both absolute rates were much higher in that study. Theoretically, if all aerobic metabolism were fueled by protein (amino acid) oxidation, the AQ would be 0.27 (Lauff & Wood, 1996; Wang et al, 2021a), so these AQ values would suggest that only 33% (present study) or 16% (Simonik & Henry, 2014) of resting metabolism is based on protein oxidation in the green crab. These values seem low relative to the few other measurements on moderately fasted carnivorous decapods, where AQs >0.135 indicated that protein was the major metabolic fuel (reviewed by Wang et al, 2021a, 2021b).…”
Section: Discussionmentioning
confidence: 75%
“…Theoretically, if all aerobic metabolism were fueled by protein (amino acid) oxidation, the AQ would be 0.27 (Lauff & Wood, 1996; Wang et al, 2021a), so these AQ values would suggest that only 33% (present study) or 16% (Simonik & Henry, 2014) of resting metabolism is based on protein oxidation in the green crab. These values seem low relative to the few other measurements on moderately fasted carnivorous decapods, where AQs >0.135 indicated that protein was the major metabolic fuel (reviewed by Wang et al, 2021a, 2021b). For example, AQ was 0.20 in both the shrimp Crangon crangon (Regnault, 1981) and the spiny lobster Sagmariasus verreauxi (Wang et al, 2021b).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…If N 2 production by gill-associated bacteria indeed accounts for a significant part of the ‘gap’ in the nitrogen balance, this would have profound implications for research into the metabolic utilization of protein in fish. For instance, when estimating the proportion of amino acid catabolism from ammonia and urea excretion (as is done for example by Wang et al (2021) ), the true extent of amino acid turnover will be underestimated since part of the catabolized amino acids will not be measurable as ammonia or urea. In contrast, if nitrogen excretion is estimated based on the difference between digested nitrogen and retained nitrogen ( Tran-Duy et al, 2008 ), the total ammonia excretion is overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, when total nitrogen is measured using conventional methods ( Kajimura et al, 2004 ), N 2 will not be detected and thus does not add up to the ‘total’ nitrogen excreted by fish. Since studies often utilize these approaches to obtain estimates of protein utilization in fish ( Lauff and Wood, 1996 ; Ferreira et al, 2019 ; Wang et al, 2021 ), to optimize feeding regimes and nutritionally balanced diets, it is key to have knowledge about the magnitude of N 2 production in fish.…”
Section: Discussionmentioning
confidence: 99%